Characteristics of Spontaneous Magnetic Field of Artificial Crack Induced by Complex Stress in Large Components. (2015) - Guo, P.J.; Guan, W.H.; Yan, C.Z.; Qin, Z.C.; Chen, X.D.
Abstract: In this study, the regularity of spontaneous magnetic field of artificial cracks in a seamless gas cylinder was investigated by metal magnetic memory technique during fatigue testing. The results showed that the regularity of magnetic signals had a strong relation with the degree of stress concentration around crack under complex stress. Moreover, the characteristic of normal component of spontaneous magnetic field H p (y) and maximum magnetic field gradient, K max, were investigated when measured perpendicular as well as parallel to the crack. It is more difficult to quantitative the crack by H p (y) signals using magnetic memory technique.